Brexit, Prorogation and Popcorn: Implications of Miller (No 2) for New Zealand - Knight, Dean R (Victoria University of Wellington Law Review, 2020)
My task in this address is to throw you into the middle of the British constitutional drama that culminated in Miller (No 2) and to try to make sense of the Supreme Court’s decision. It is a decision that has polarised public law experts: it has been both celebrated and condemned. Thus, there is some work to understand the decision in its extraordinary context, explore its implications for Westminster constitutionalism and speculate on what sort of precedent it sets for judicial review of the prerogative. Importantly for this audience, I would like to reflect on the relevance to us, sitting, as we do, over 10,000 miles from the drama in Westminster. In other words, I would like to test the New Zealand "what if?" question. Could a similar meltdown happen here? And, if so, how would our constitutional agents react?